Evaluation of accessibility commuter-line station with jitney transportation modes by using GIS application: a case study of Depok Station - Hardiyansyah, Bayu Alif; Sutikno, Fauzul Rizal; Zeibots, Michelle; Wijayaratna, Kasun De Silva (Civil and Environmental Science Journal (CIVENSE), 2023)
This research aims to evaluate the aspects that can increase the Station's service area by maximising the integrated Jitney as the other public transportation modes that can increase reachability for the people near the Station. Evaluating the accessibility of some stations in the Depok area is needed to identify the infrastructure upgrading priorities, such as providing pedestrian roads and giving better access to the Station to increase the Station's service area. The methodology used in this research is analysing method using a GIS application to assess and discover the pattern of travel behaviour for public transport in the Depok municipality area. The GIS Database Design in this research uses the Spatial Database and Attribute Database, which are integrated with the QGIS application to become Maps for the service area of public transportation in the Depok Municipality. The road network in Depok municipality is dominated by the jitney route as intracity public transportation, which travels on the arterial and collector road. Then the railway is located in the central area of Depok that stretches from South to North. There are some areas that do not have access to jitney services due to this residential area being far from the arterial and collector road travelled by Jitney. Looking at its planning for jitneys in the Depok area, the availability of jitneys follows the demand of the passenger population, and there are no travel analyses from the Transportation Department of Depok Municipality or local public transport organisations (ORGANDA) as private jitney operators. The ineffective jitney route planning is the other reason that there are some uncovered residential areas from public transport access. Subsequently, there are different travel time characteristics among four commuter line stations in the Depok Municipality area. The Citayam and New Depok Stations have wider access for pedestrians which these two stations have a more extensive service area than Old Depok Station, whereas Old Depok Station has restricted access to the west area of this Station. The rearrangement of the Station access is needed, especially for Old Depok Station, by adding road access on the west side to increase the service area of the Station.